ZOOM FATIGUE IN PAKISTANI UNIVERSITY TEACHERS - Khan, Muhammad Umar; Saeed, Shehwar; Abbas, Qasir (Pakistan Journal of Psychology, 2023)
Objectives: Zoom fatigue defines as the tiredness, worries, or exhaustion that is caused by overuse of computer-generated ways of communication. The present investigation focused on random issues arisen due to long-term use of zoom meetings. It was explored how zoom influences university teachers socially, emotionally, physically and mentally. Difficulties regarding effectiveness of education due to usage of zoom platform were examined Design of the study: Qualitative research design followed by thematic analysis technique was core paradigm of the study. Place and Duration: Data collection was carried out from Universities of Faisalabad, Sargodha and Lahore districts of Punjab province of Pakistan from June 2021 to August 2021. Sample and Method: The purposive sample comprising (n=20) participant who taught at university level with only zoom platform were included using semi-structured interviews. Results and Conclusion: Study emerged 07 themes and 23 subthemes. Themes appeared in the study include zoom utilization challenges, physical health issues, psychological concerns, connectivity fret, home life and social life disturbances and participants showed preferences for on-campus classes. In Pakistan, random ethical violations by students were most common and zoom has seen as ineffective mode of learning particularly for poor signal coverage area inhabitants. However, some already known factors have been highlighted by this study as internet and health related matters.